Validation of Wound-QoL Questionnaire among Patients with Acute Wounds in Enugu, South-east Nigeria (African Journal of Biomedical Research, 2023)
Globally, health related quality of life (HRQoL) has become an essential wound outcome measure in evaluating holistic care, clinical practice and research. In Nigeria, there is a dearth of validated studies on standardised instruments to assess quality-of-life in patients with acute wounds. This study validated the Wound-QoL questionnaire in Nigeria. It was a single-blinded randomized controlled study, carried out amongst 42 participants using simple blocked randomization to assign patients to different groups (Biodress, honey and povidone-iodine). Wound-QoL was used for data collection with due ethical consideration and data analysis. The median age of the participants was 32.5 years, with a slight male preponderance (52.4%). The global score was above 0.7 at both times tested with the subscale scores ranging from 0.420 to 0.754. The mean values for both Wound-QoL global scores (T0: 0.83, T1: 0.79) and two subscale scores (body: T0: 1.28, T1: 1.17, everyday life: T0: 0.61, T1: 0.58) decreased over time while the psyche subscale remained unchanged (T0: 0.53, T1: 0.53). On item selectivity, the global score was significantly correlated to each of the items and the subscales. This result showed that acute wounds affect patients’ quality of life. It also indicates that the Wound-QoL questionnaire has positive psychometric properties. The Wound-QoL is a valid and reliable tool in assessing quality of life of people with acute wounds in Nigeria.  A large-scale study in different regions of the country is recommended bearing in mind the cultural differences.